Psychometric properties of the DY-BOCS in a Turkish sample of children and adolescents - ERDOĞDU, AYŞE BURCU (W B SAUNDERS CO-ELSEVIER INC, 2016)
Background: Dimensional Yale-Brown Obsessive-Compulsive Scale (DY-BOCS) is a promising scale for assessing frequency and severity of symptom dimensions. The main objective of the study was to assess the psychometric properties of the DY-BOCS in a large sample of children and adolescents from Turkey. Methods: We studied 143 children and adolescents, 7-18 years, with well characterized DSM-IV-R OCD, ascertained from seven collaborating university or state hospital sites. We compared the DY-BOCS scores with the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS), the Children's Depression Inventory (CDI), the Yale Global Tic Severity Scale (YGTSS) and the Child Behavior Checklist 6-18 years (CBCL 6-18). Results: The internal consistency of the DY-BOCS symptom dimensions and inter-rater agreement of component scores were excellent. The agreement between global DY-BOCS score and the total CY-BOCS score was highly significant (Pearson's r = 0.55, p < 0.0001). Severity scores for individual symptom dimensions were independent of one another, only modestly correlating with the global ratings, and were also differentially related to ratings of depression, anxiety and tic severity. Conclusion: The DY-BOCS is a reliable and valid instrument for assessing multiple aspects of OCD symptom severity in children and adolescents from Turkey. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: OBSESSIVE-COMPULSIVE DISORDER; SEROTONIN REUPTAKE INHIBITORS; SYMPTOM DIMENSIONS; FOLLOW-UP; SCALE; PREDICTORS; ANXIETY; RELIABILITY; DEPRESSION; STABILITY